Ghrelin regulating liver activity and its potential effects on liver fibrosis and Echinococcosis - Zhu, Jiang; Zhou, Tanfang; Menggen, Meng; Aimulajiang, Kalibixiati; Wen, Hao (Frontiers in Cellular and Infection Microbiology, 2024)
Ghrelin widely exists in the central nervous system and peripheral organs, and has biological activities such as maintaining energy homeostasis, regulating lipid metabolism, cell proliferation, immune response, gastrointestinal physiological activities, cognition, memory, circadian rhythm and reward effects. In many benign liver diseases, it may play a hepatoprotective role against steatosis, chronic inflammation, oxidative stress, mitochondrial dysfunction, endoplasmic reticulum stress and apoptosis, and improve liver cell autophagy and immune response to improve disease progression. However, the role of Ghrelin in liver Echinococcosis is currently unclear. This review systematically summarizes the molecular mechanisms by which Ghrelin regulates liver growth metabolism, immune-inflammation, fibrogenesis, proliferation and apoptosis, as well as its protective effects in liver fibrosis diseases, and further proposes the role of Ghrelin in liver Echinococcosis infection. During the infectious process, it may promote the parasitism and survival of parasites on the host by improving the immune-inflammatory microenvironment and fibrosis state, thereby accelerating disease progression. However, there is currently a lack of targeted in vitro and in vivo experimental evidence for this viewpoint.